Ragam Hias Nusantara - Kuntjoro-Jakti, R.A. Diah Resita I. (Bina Nusantara University, 2010)
Considering subsided natural resources, creative economic is a choice and proclaimed by Indonesian government on 2008. Design is one of creative economic components that has critical part in showing Indonesia?s identity in worldwide. So, Indonesian motifs as national culture richness played as a determined part in comparison between Indonesia and other nation?s masterpiece. This article is the first part from four parts. This part focuses more in describing basic visual art that becomes the strength of Indonesian motif design: dot and line, shape, texture, and colour.